2001
DOI: 10.1097/00007632-200104010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Postural Control of the Lumbar Spine Is Associated With Delayed Muscle Response Times in Patients With Chronic Idiopathic Low Back Pain

Abstract: Patients with chronic low back pain demonstrated poorer postural control of the lumbar spine and longer trunk muscle response times than healthy control volunteers. Correlation between these two phenomena suggests a common underlying pathology in the lumbar spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
336
5
29

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 503 publications
(404 citation statements)
references
References 29 publications
21
336
5
29
Order By: Relevance
“…short-term and long-term stability exponents. Only the short term exponent, H S , has been shown to discriminate between subject groups with and without low-back pain (Radebold et al, 2001). Therefore, only the short-term exponent was used in the present analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…short-term and long-term stability exponents. Only the short term exponent, H S , has been shown to discriminate between subject groups with and without low-back pain (Radebold et al, 2001). Therefore, only the short-term exponent was used in the present analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, empirical assessments of stabilizing neuromuscular control of the torso have only recently become available. Radebold et al (2001) had patients with low-back pain maintain seated balance on a wobbly chair by means of torso movement. Stability was quantified by summary statistics of movement variability and by nonlinear time-series analyses of movement response recorded during the task (Cholewicki et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Three general aspects of altered muscle recruitment patterns in people with back pain have been investigated: (1) altered muscle activation patterns, especially coactivation, in a static task such as pulling against a fixed object or slow lifting [1,3,19,20,28], (2) altered muscle reflex latency times in response to a sudden perturbation [26] or dropped weight [18,32], quick release of trunk loading [27], or moving support platform [10], (3) altered muscle activation pattern in anticipation of an unexpected or voluntary perturbation [14,25].…”
Section: Introductionmentioning
confidence: 99%
“…LBP is a widespread pathological condition that is often related to impaired or degenerated trunk mobility, which becomes evident during common activities [39,40]. Taimela et al reported that lumbar muscle fatigue impaired lumbar positional sense in both patients with LBP and healthy subjects [41].…”
Section: Sensory Proprioceptive Inputs In Postural Controlmentioning
confidence: 99%